Desenvolvimento de procedimentos automáticos para determinação fotométrica de alumínio em água potável e etanol em vinhos empregando o processo de multicomutação em análise em fluxo - Brandão, Eliel Guimarães (Universidade Federal de São Carlos, 2024)
The quality of drinking water is crucial for public health, as is the quality of wines for the food industry. Aluminum, which poses health risks such as neurological disorders, has a maximum allowable limit of 200 µg L-1 in drinking water, according to the WHO. The ethanol concentration in table wines, important for their regulation and quality, must be between 8.6 and 14% (v/v). Accurate and efficient analysis methods are essential to ensure consumer safety and compliance with regulatory standards. The study proposes to develop automatic analytical procedures, using flow analysis, to determine aluminum in drinking water and ethanol in wine, aiming to reduce waste and optimize productivity. The system for determining aluminum consists of a fluid propulsion module (minipumps), agitation (flow-batch) and detection system (photometer) with light-emitting diode (LED, λ = 534 nm). To determine ethanol in wines, the system consists of a vapor drag module (purge), fluid propulsion (minipumps) and detection system (photometer) with light-emitting diode (LED, λ = 570 nm). Both systems controlled by an Arduino Due microcontroller, equipped with the necessary interfaces and running software written for this purpose. After selecting the best operating conditions, the effectiveness of the proposals was evaluated: (1) for the determination of aluminum in drinking water, the recovery range was 93 to 128%, linear response in the range of 50 to 400 µg L-1 (R2 = 0.9994); detection limit of 61.29 µg L-1; consumption of chromium azurol S 20 µg per determination, coefficient of variation 1.26%; and analytical frequency of 30 determinations per hour; (2) to determine ethanol, the paired t test was used (n = 8) with tcal = 1.948, with no significant difference with the reference method (densimetry), linear response in the range of 2.5 to 20% (v /v) (R2 = 0.9989); detection limit of 0.0974 µg L-1; K2Cr2O7 consumption 17.65 mg per determination, coefficient of variation 4.14%; and analytical frequency of 60 determinations per hour. Both procedures developed demonstrated that the proposed analytical procedure for determining aluminum in drinking water is effective and meets the requirements of regulatory agencies, such as CONAMA, FUNASA and WHO, which establish a limit of 0.2 mg L-1. Likewise, the method for determining the ethanol content in table wines proved to be valid when compared with the official reference method, proving to be practical and efficient.
Development of automatic procedures for photometric determination of aluminum in drinking water and ethanol in wine using the multi-commuting process in flow analysis
Keywords: Instrumentação analítica; Análise por injeção em fluxo; Flow-batch; Vinho; Etanol; Alumínio; Água potável; Analytical instrumentation; Flow injection analysis; Flow-batch; Wine; Ethanol; Aluminum; Potable water; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA